PROPOSED SANCTIONS FOR PROFESSIONALISM LAPSES BY THE STUDENTS AND THE STAFF IN TWO PAKISTANI MEDICAL COLLEGES: Proposed Sanctions For Professionalism Lapses - Shukr, Irfan; Choudry, Abeera; Safdar, Aqeel (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the proposed level of sanctions by the students and the staff for professionalism lapses related to academic integrity in two Pakistani medical colleges. Study Design: Cross sectional study. Place and Duration of Study: Private Medical Colleges in the year 2013. Material and Methods: A stratified sample of 520 students, and 60 faculty members were invited to participate in this cross sectional study. A validated and customized version of Dundee Poly-professional Inventory–1 for use in Pakistani medical schools was used. The students were asked to indicate the appropriate level of sanctions (1-10) that should apply for the first time offence without circumstances that lessen the gravity of the offence. Results: The response rate of students and faculty was 92%, and 62% respectively. There was statistically significant difference between the students and the faculty (p<0.05) in recommended severity of punishment for 31 (68%) offences. Students considered that no punishment should be given for completing work for another student; accessing not permitted old exam papers or course work to assist in study; and photographing dissection or pro-section or cadaver material, whereas faculty thought these behaviors were punishable. They were stricter on recommended sanction for drinking alcohol over lunch and interviewing a patient in afternoon, by two levels. The faculty was more severe on punishments by at least one level for rest of the unprofessional behaviors. Conclusion: Pakistani faculty perceived the majority of behaviors more severely as compared to the students. Dundee Poly Professionalism Inventory-I can be used in Pakistan, and other South Asian countries to measure perceptions of severity of unprofessional behaviors related to academic integrity, that can help in forming code of conduct.